Biosorption of Some Heavy Metal Ions (Pb2+, Cd2+, Ni2+) From Aqueous Solution by Malicorium - MOMEN HERAVI, M.; MOHAJERI, M.; ARDALAN, P.; ARDALAN, T. (Asian Journal of Chemistry, 2010)
In this study, removal of some heavy metal ions such as Pb2+, Cd2+, Ni2+ from aqueous solution has been investigated by using malicorium as natural adsorbent. The research is a bench scale experimental type and analyses have performed by using different amounts of adsorbent in solutions with 5 different concentrations of each metal ions. Besides, the effect of various amounts, size of malicorium used and pH in biosorption efficiency experiments has been investigated. Results from this work have indicated that (a) the removal efficiency is highest for lead and is minimum for nickel. About 98 % Pb2+ were achieved by using 2.5 g absorbent having concentration of 100 mg/L Pb2+. For Cd2+ and Ni2+, the efficiency were 83 and 43 %, respectively in the same condition, (b) optimal efficiency obtained in 30-100 mesh size particles for all three ions, (c) maximum biosorption occurred at pH = 12 for Ni2+ and Cd2+ but for Pb2+ it happens at acidic pH.